Developing a telemedicine value co-creation framework : patient perceptions of the telemedicine model of care delivery - Swan, Eric (UW-Whitewater, 2019)
Technology is reshaping the patient–provider relationship. Digital health tools such as electronic medical records, patient portals, and telemedicine provide patients the opportunity to engage with healthcare systems remotely at their convenience. Telemedicine, a platform that allows patients to be seen by a provider remotely with audio and video capabilities, shows great potential for the future of healthcare delivery with increased access, convenience, continuity of care, and cost savings. While there is strong promise for telemedicine, implementation by healthcare organizations and adoption by patients have been slower than expected. Previous research has examined telemedicine usage through the technology acceptance model (TAM) and diffusion of innovation (DOI). While these theories have found initial results, they lack in providing conceptual and empirical frameworks that explain value creation and the relational elements of telemedicine. This research builds upon these theories, using elements of TAM, DOI, and SERVQUAL to develop factors exploring patients’ attitudes towards telemedicine usage. Two theoretical models are proposed and examined, utilizing service dominant logic (SDL) to extend our knowledge of the role of the patient as value co-creator. Specifically, this study tested the direct relationships of six attitudinal factors that influence patients’ likelihood to use telemedicine. In addition, the examination of antecedents and relationships of telemedicine attitudes provided further insights into the complex nature of digital health. Multiple linear regression and structural equation modeling (SEM) provided analysis of survey results from over 1,000 healthcare patients exploring value co-creation in the telemedicine context. This study provides implications for marketing and health literature regarding value co-creation in telemedicine. First, this study offers empirical insights into patients’ attitudes towards telemedicine. Previous studies have not fully examined the impact of patient attitudes on telemedicine usage. In addition, patient attitudinal measurement items were developed and tested that can be utilized for future research. Second, SDL foundational premises offer insights into telemedicine value creation through the lens of the patient. Specifically, this study explored the role of the patient as value co-creator, determiner of value, resource integrator, and initiator of propositions as value-in-use. Further, this study examined the role of value proposition configurations in the development of telemedicine value co-creation. Third, results indicated patients’ technological savviness significantly influences all telemedicine usage attitudes in the Model 2 framework, including relative service quality, access, care uses, impact on patients, and likelihood to use. These findings align with SDL, recognizing the importance and role of patients’ operant resources in value determination and usage decision-making. Finally, the examination of antecedents and relationships of telemedicine provides further knowledge into the multi-faceted and complex telemedicine decision-making process.
This file was last viewed in Adobe Acrobat Pro.
Keywords: Telecommunication in medicine; Patients--Attitudes; Medical care; Physician and patient